Activating Effect of 3‐Benzylidene Oxindoles on AMPK: From Computer Simulation to High‐Content Screening - Novikova, Daria S.; Grigoreva, Tatyana A.; Ivanov, Gleb S.; Melino, Gerry; Barlev, Nickolai A.; Tribulovich, Vyacheslav G. (ChemMedChem, 2020)
AMP‐activated protein kinase (AMPK) is currently the subject of intensive study and active discussions. AMPK performs its functions both at the cellular level, providing the switch between energy‐consuming and energy‐producing processes, and at the whole body level, particularly, regulating certain aspects of higher nervous activity and behavior. Control of such a ‘main switch’ compensates dysfunctions and associated diseases. In the present paper, we studied the binding of 3‐benzylidene oxindoles to the kinase domain of the AMPK α‐subunit, which is thought to prevent its interaction with the autoinhibitory domain and thus result in the AMPK activation. For this purpose, we developed the cellular test system based on the AMPKAR plasmid, which implements the FRET effect, synthesized a number of 3‐benzylidene oxindole compounds and simulated their binding to various sites of the kinase domain. The most probable binding site for the studied compounds was established by the correlation of calculated and experimental data. The obtained results allow to analyze various classes of AMPK activators using virtual and high‐content screening. Content counts: The binding site of 3‐benzylidene oxindoles within the kinase domain of AMP‐activated protein kinase (AMPK) was established by correlating calculated and experimental activities. Such binding to the kinase domain leads to AMPK activation. A cell model based on the FRET effect was used under HCS conditions to evaluate target activity.